Estimation of Chronological Age from Advanced Glycation End Products Level in Vitreous Fluid - Kanicnan Intui; Churdsak Jaikang; Somlada Watcharakhom; Yutti Amornlertwatana (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Chronological age estimation is an important process for corpse identification. Advancedglycation end products (AGEs) are accumulated during lifetime and have been used for forensic identification.The AGEs in vitreous humor still lack of information for age estimation. Objective: To investigate correlationbetween the AGEs level contained in vitreous humor and chronological age in postmortem cases. Methods:The vitreous humor samples were collected from the postmortem cases (n=142). The AGEs levels weredetermined by spectrofluorometer and presented in microgram of quinidine hemisulfate equivalent (?g QE/mL) and nanogram of pentosidine equivalent (ng PE/mL). Stepwise linear regression was used to generatethe equation. Results: The QE and PE showed mild positive correlation (r = 0.350 and 0.195; p <0.001,respectively) while the PE/QE ratio showed moderate negative correlation with age (r = -0.561, p <0.001).The predicted equation showed error value 12 years and gave accurate prediction in range 40-59 years old.Conclusion: The AGEs contained in the vitreous humor correlated with chronological age in postmortemcases. The other fluorescence molecules might be interfere during the AGEs measurement then the specificmethods should be developed for measuring the AGEs level to decrease the error value.